Performance optimization of a Joule-Brayton engine based on the efficient power criterion - Yilmaz, T. (SAGE PUBLICATIONS LTD, 2007)
The proper optimization criteria to be chosen for the optimum design of heat engines may differ depending on their purposes and working conditions. If the heat engine design was done not to obtain maximum work or power, but to have maximum benefit from energy, then the design objective is to get maximum efficiency. In this study, a new performance analysis is applied to a reversible Joule-Brayton cycle based on a new criterion which is proposed for all kind of heat engines. The proposed criterion, called efficient power, is defined as the multiplication of power by efficiency. Therefore, this criterion considers not only the power output but also the cycle efficiency. Maximizing the efficient power function gives a compromise between power and efficiency. The results showed that the design parameters at maximum efficient power (mep) conditions lead to more efficient engines than that at the maximum power conditions and that the mep criterion may have a significant power advantage compared to the maximum power density criterion.
Keywords: performance optimization; power; power density; Joule-Brayton; ECOLOGICAL OPTIMIZATION; DENSITY; Thermodynamics; Engineering